Unmaturing the telecom industry - Santos, Sebastião Alves Oliveira Silva (2020)
Conducted between June 2019 and January 2020, the present report studies the intrinsic value of AT&T Inc.’s share price as part of an investment decision. The report underlines the importance that developing 5G will have not only in the firm, but in the telecommunications industry as a whole, along with the importance of AT&T being able to diversify in terms of its business combination to present positive and strong growth prospects, while inserted in a mature industry. The report thoroughly mentions the advantages and concerns around the disruptive addition of Warner Media to the firm’s business, the use of data analytics and a wide consumer base to develop and introduce new advertising solutions and, the innovation of its traditional mature industry with the 5G development. After quantifying the mentioned characteristics of AT&T and the segments it operates in, measuring the risk and required return on the company, and applying the Discounted Cash-Flow method (DCF), the following report concludes that the future prospects for AT&T’s business justify a BUY recommendation for its stock, as part of an investment decision.